Educational level and decreases in leisure time physical activity: predictors from the longitudinal GLOBE study. Issue 8 (1st August 2001) - Droomers, M; Schrijvers, C T M; Mackenbach, J P
Abstract : STUDY OBJECTIVE: This study describes educational differences in decreases in leisure time physical activity among an adult, physically active population and additionally attempts to identify predictors of these differences from information on health status and individual and environmental factors. DESIGN: Prospective population based study. Baseline measurement were carried out in 1991 and follow up in 1997. SETTING: South eastern part of the Netherlands. PARTICIPANTS: The study included 3793 subjects who were physically active in 1991 and who participated in the follow up. METHODS: Potential predictors of decreasing physical activity were measured in 1991. Logistic regression analyses were carried out for two age groups (<45 years; ⩾45 years) separately. MAIN RESULTS: Lower educated respondents experienced statistically significant higher odds to decrease physical activity during follow up, compared with respondents with higher vocational schooling or a university degree. Perceived control was the main predictor of educational differences in decreasing physical activity in both age groups. In the older group, material problems and a poor perceived health experienced by lower educated people additionally predicted educational differences in decreases in physical activity during leisure time. CONCLUSIONS: These findings have important implications for health promotion practice and policy to prevent socioeconomic differences in physical inactivity and health. There is a need for evidence-based interventions that improve perceived control and reduce material problems in lower educated groups.